Independence of the Auditor in Private Joint-Stock Companies A Comparative Study An Exploratory Research - Abdulqader, Prof.Dr. Dana Hama Baqi Abdulqader; Ahmed, Asst.L. Liza Ata Abdulhakim Ahmed (Sulaimani Journal for Humanities, 2025)
Private joint-stock companies include a large number of natural and legal persons, in addition to dealing with investors, creditors, and other stakeholders. Protecting these parties from fraud, conflicts of interest, and mismanagement is of utmost importance. To achieve this goal, external auditing conducted by the auditor serves as an effective mechanism to verify the accuracy of financial statements and their compliance with the law and the company’s articles of association. The independence of the auditor is a key guarantee for performing their role objectively and professionally. Accordingly, this study seeks to identify the shortcomings in the Iraqi legal system and propose recommendations to enhance the independence of the auditor, ensuring the fulfillment of their duties without external influences or pressures. This, in turn, strengthens the confidence of shareholders and other stakeholders in the company.